(untitled) (Bioscience Journal, 2014)
Jatropha curcas (Euphorbiaceae) is an evergreen tree traditionally used in popular medicine, and also as a promising source for bio-fuel production. The in vitro propagation of this species has been studied as an alternative to conventional methods such as cutting and seedling. In vitro culture environment consists on closed flasks, with high relative humidity, reduced gas exchanges and artificial temperature and luminosity conditions. These conditions may induce physiological and anatomical alterations in cultivated plants. The occurrence of anatomical alterations on the leaves of J. curcas was examined in plants cultivated both in vitro and ex vitro, under greenhouse conditions. The stomatal index was higher on the leaves from greenhouse plants. Mesophyll thickness did not differ, but the greenhouse leaves presented an additional palisade layer, which reflects the environmental influence on cell division. The cells of the chlorophyllous parenchyma of young plants grown in greenhouse conditions have larger chloroplasts than those of the plants grown in vitro. The chloroplasts of mature leaves are similar in height, but the mitochondria are smaller. Current results indicate that the leaves of J. curcas respond distinctly to both environments. It is necessary to adjust the abiotic conditions in vitro to avoid precocious senescence, diagnosed by chloroplasts and mesophyll degradation.